Lipoma management with a minimally invasive 1,444 nm Nd:YAG laser technique - Piccolo, Domenico; Mutlag, Mohammed Hussein; Pieri, Laura; Fusco, Irene; Conforti, Claudio; Crisman, Giuliana; Bonan, Paolo (Frontiers in Medicine, 2022)
Background Lipoma is the most common benign mesenchymal tumor that is composed of mature fat cells. Subdermal laser lipoma treatment may be recommended as an alternative to surgery for its removal. Purpose The purpose of the study was to investigate the efficacy of the 1,444 nm Nd:YAG laser subcutaneous intralesional application as a treatment option for lipoma. Materials and methods On 60 patients (37 women and 23 men) with lipomas localized above the muscle and lipomatosis in various regions, a subcutaneous, micro-pulsed 1,444 nm Nd:YAG laser procedure was executed. Before treatment, an ultrasound was performed and the lipomas were measured. The same lighting setup and photographic tools were used to take pictures of each patient. Results The lipoma reduced or completely disappeared in all cases at the last follow-up, and no infections, burns, skin lesions, episodes of severe bleeding, or other serious adverse effects were reported. The most common transient side effects were ecchymosis and edema. Partial lesion reduction refers to rare cases of lipomatosis in which the lipomas were so small that suction and accurate positioning of the capsular membrane contours were impossible. Conclusion Lipoma treatment with a 1,444 nm Nd:YAG laser is a safe and effective minimally invasive procedure without risk of scarring. For cellular disruption, laser treatment is an effective and safe option.